ZnO thin films deposition for the manufacture of (VOCs) gas sensor - Hadjari, Chaima; Benmessaoud, Halima; Abdellah, Rahmani (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
Volatile organic compound (VOCs) are the main sources of pollutants in the indoor environment and are considered to be very harmful to the human body. Therefore, more work is needed regarding the detection and development of vapor detection methods. In this study, we have developed thin layers of zinc oxide (ZnO) on a silicon substrate using the spray pyrolysis technique. The deposition conditions such as the distance between the spray nozzle and the substrate, deposition temperature, and molarity of the solution were carefully controlled. The ZnO deposit was used to build a gas sensor capable of detecting vapors of volatile organic compounds. The spray pyrolysis technique is a simple and cost-effective method that is easy to implement. The optical and structural properties were investigated using UV-Visible spectrophotometry and X-ray diffraction (DRX). We specifically investigated the detection properties of the ZnO film for different VOCs type. The results indicated that the ZnO-based sensors exhibited higher sensitivity towards acetone vapor (VOC) compared to the other two tested VOCs, namely ethanol and methanol.
OPTION: Instrumentation